Una Hunt, Sources and Style in Moore’s Irish Melodies (2017) - McAulay, Karen (Journal of the Society for Musicology in Ireland, 2019)
A review of Una Hunt, Sources and Style in Moore’s Irish Melodies (London: Routledge, 2017). ISBN 978-1-409-40561-0; ISBN 978-0-367-23145-3; ISBN 978-1-315-44300-3